2009
DOI: 10.1002/fuce.200800100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CeO2 on Pt/CeO2/CNT catalyst for CO electrooxidation

Abstract: Pt/CeO2/CNT catalysts were prepared by adsorbing Pt nanoparticles on the supports of CNTs coated with CeO2. The electrocatalytic performances in respect to the electrooxidation of chemisorbed CO were tested using potential step and stripping voltammetry methods under variable sweep rate and temperature conditions. At 10 mV s–1, the CO stripping voltammogram exhibited the peak splitting phenomenon. The oxidation charge and the peak potential of the two voltammetric peaks changed regularly with the number of Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…For Pt/MnO 2 / CNTs, the CO electro-oxidation peak was split, instead of one voltammetric peak. The occurrence of the peak splitting may be explained by the participation of hydroxyl groups on MnO 2 , similar with the voltammetric behaviour on PtRu electrode [22]. The peak potential of CO electro-oxidation for Pt/RuO 2 -MnO 2 / CNTs (0.42 V) is also lower than that of Pt/MnO 2 /CNTs (0.57 and 0.68 V).…”
Section: Co and Methanol Electrocatalytic Oxidation Activity Of Pt/rumentioning
confidence: 67%
See 2 more Smart Citations
“…For Pt/MnO 2 / CNTs, the CO electro-oxidation peak was split, instead of one voltammetric peak. The occurrence of the peak splitting may be explained by the participation of hydroxyl groups on MnO 2 , similar with the voltammetric behaviour on PtRu electrode [22]. The peak potential of CO electro-oxidation for Pt/RuO 2 -MnO 2 / CNTs (0.42 V) is also lower than that of Pt/MnO 2 /CNTs (0.57 and 0.68 V).…”
Section: Co and Methanol Electrocatalytic Oxidation Activity Of Pt/rumentioning
confidence: 67%
“…At low potentials (<0.29 V), when methanol contacts with Pt, the dissociative adsorption of methanol on Pt via a stepwise dehydrogenation forms CO species attached to the surface of Pt sites, poisoning Pt sites [22,36]. The reaction equation can be written as Eq.…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the catalyst activity, the third metal, such as Ru [21], Ni, P and Ir [29][30][31], was added to the binary PtSn catalyst and showed a superior performance. And many oxides of rare earth element with abundant d-orbit such as LnO x (Ln = Sc, Y, La, Ce, Pr and Nd) [32][33][34] were also used to synthesise the Pt-based catalysts for ethanol or methanol electrooxidation. However, the performance of PtSn catalyst modified by rare earth oxides is little reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hayden et al [19] have demonstrated that the particle size of active component and the substrate have great effect on the CO electrocatalytic activity over AuNPs. In addition, the shape effect of carbon material [20][21][22][23][24], such as carbon nanofibers, carbon nanotubes, or ordered mesoporous carbons on the catalytic performance for CO electrooxidation have been widely investigated. Xu et al [25] presented a detailed comparison between multi-walled (MWNT) and single-walled carbon nanotubes (SWNT) for CO-stripping and found a higher tolerance to CO poisoning of Pt in Pt-SWNT/Nafion.…”
Section: Introductionmentioning
confidence: 99%